3D Gait Analysis and Patient-reported Outcomes of Femoral Osteotomies for Torsional Deformity. Issue 9 (15th October 2022) - Hamid, Jehan; Do, Patrick; Bauer, Jeremy
Abstract : Background: Idiopathic torsional deformities causing pain and/or functional difficulty is an indication for a femoral derotational osteotomy (FDRO). Past studies have focused entirely on children with internal femoral torsional deformity (IFTD). This study aims to compare gait and outcomes between children with IFTD and those with external femoral torsional deformity (EFTD) after a FDRO. Methods: A retrospective review of all patients who underwent an FDRO between 1997 and 2020 at our institution. Data on typically developing (TD) children with no torsional deformity was used as a control group. We analyzed preoperative and postoperative standardized physical examination, 3-dimensional gait analysis, and Pediatric Outcomes Data Collection Instrument questionnaires. Results: There were 54 patients in total (IFTD=37, EFTD=17) and 20 patients in the control group. The EFTD cohort was older (IFTD=11.7, EFTD=14.7, P <0.05) and had a higher body mass index both preoperatively (IFTD=21.1 kg/m 2, EFTD=32.1 kg/m 2, P <0.05) and postoperatively (IFTD=20.2 kg/m 2, EFTD=34.1 kg/m 2, P <0.05). Preoperatively, 3-dimensional gait analysis elicited mean hip rotation in stance was more internal for IFTD cohort (10.8 degrees) and external for the EFTD cohort (−17.8 degrees) in comparison to the TD (2.4 degrees, P <0.001). Postoperatively, dynamic mean hip rotation during stance was −1.4 degrees for IFTD, whereas for EFTD, it was −5.4 degrees, which was different to the TD ( P <0.05). The IFTD group's Pediatric Outcomes Data Collection Instrument improved for transfer/basic mobility, sports/physical function, global functioning, and satisfaction with symptoms ( P <0.05). The EFTD group that only reported an improvement with the satisfaction with symptoms after surgery ( P <0.05). Conclusions: Adolescents with surgically corrected IFTD show more improvement in gait and in patient-reported outcomes than those with surgically corrected EFTD. Children with EFTD persist in external rotation and have less satisfactory patient-reported outcomes after a FDRO in comparison those with IFTD. Level of Evidence: Level III—retrospective comparative study